UK Defamation Act 2013: Key Changes - LOW, Kee Yang (Institutional Knowledge at Singapore Management University, 2014)
The much awaited new legislation affecting English defamation law received Royal Assent in April 2013, ushering in changes substantive as well as cosmetic. Some of the substantive changes are radical and reflect the increasing emphasis on the right of freedom of expression. This comment deals with the key changes brought about by the new Defamation Act 2013.